Distribution of Labeled Embryonic Nerve Cells After In Vivo Introduction at Experimental Eye Trauma - Demin, Yu. A.; Litvinova, L. V. (Problems of Cryobiology and Cryomedicine, 2007)
The distribution of cryopreserved embryonic nerve cells labeled with 3,3’-dioctadecyloxacarbocyanide bromide (DDC) in the tissues of retinal and vascular membranes after introduction at experimental laser burn of eye retina in rabbits has been studied. The presence of dye in the damage focus for 21 days has been shown.